2021
DOI: 10.1016/j.ijid.2020.10.049
|View full text |Cite
|
Sign up to set email alerts
|

HIV/SARS-CoV-2 co-infection: T cell profile, cytokine dynamics and role of exhausted lymphocytes

Abstract: Highlights HIV-1 and SARS-CoV-2 are likely to exhibit a synergic effect on immunity in serious cases of HIV/SARS-CoV-2 co-infection. Exhausted T lymphocyte dynamics along with IL-10 and TGFβ growth during COVID-19 course may be an effective prognostic marker of this synergy as well as overall prognosis of the co-infection disease. HIV without antiretroviral therapy may be a dangerous comorbidity of COVID-19. Conversely, COVID-19 clinical course and immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 32 publications
4
46
2
3
Order By: Relevance
“…Plasma cell and T cell counts were measured on Days 8–12 in serum and pharyngeal mucosa-associated lymphoid tissue (MALT). As we found in another study of a relatively small group of HIV/SARS-CoV-2 co-infected people, the maximum of T cell response to SARS-CoV-2 acute infection is usually observed since Day 6 to 16 34 . As well, PaO 2 /FiO 2 ratio was measured on Days 8–12 (1) to correspond roughly with T cell measurements; and (2) since it was demonstrated by different groups of researchers that severe COVID-19-associated ARDS is generally detected after the first week of the COVID-19 disease 35 38 .…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…Plasma cell and T cell counts were measured on Days 8–12 in serum and pharyngeal mucosa-associated lymphoid tissue (MALT). As we found in another study of a relatively small group of HIV/SARS-CoV-2 co-infected people, the maximum of T cell response to SARS-CoV-2 acute infection is usually observed since Day 6 to 16 34 . As well, PaO 2 /FiO 2 ratio was measured on Days 8–12 (1) to correspond roughly with T cell measurements; and (2) since it was demonstrated by different groups of researchers that severe COVID-19-associated ARDS is generally detected after the first week of the COVID-19 disease 35 38 .…”
Section: Methodssupporting
confidence: 67%
“…We may define it as where RR is respiratory rate [min –1 ]. The detailed description of this indicator is provided in our another work 34 . An advantage of using AS over any of PaO 2 /FiO 2 ratio, SpO 2 or RR can be explained by the complex nature of AS .…”
Section: Methodsmentioning
confidence: 99%
“… 36 , 37 Similarly, untreated HIV infections might worsen the immunological effect of COVID-19 infection. 38 At present, effective ART is universally recommended and immunological recovery is expected in most patients with HIV infection, 39 but COVID-19 might occur in people living with HIV unaware of their HIV status. In the largest published cohorts, the potentially higher risk for poorer COVID-19-related outcomes in people living with HIV with lower CD4 cell counts 40 , 41 might be driven by concomitant comorbidities, 42 more common in people living with HIV than in uninfected people, 43 the prevalence of which is inversely proportional to CD4 counts in people living with HIV.…”
Section: Pathogenesismentioning
confidence: 99%
“…Only two studies have measured the effect of HIV-1 infection on the overall profile of T cells in COVID-19 cases: Karim et al showed that viraemic HIV-infected COVID-19 patients exhibited lower frequencies of tissue homing CXCR3+ CD8 T cells and higher T cell activation compared to HIV-uninfected patients (Karim et al, 2020). Similarly, Sharov showed that viraemic HIV-infected COVID-19 patients displayed enhanced exhaustion of their T cell compartment (Sharov, 2020). This suggest that systemic immune activation associated with untreated HIV could skew the SARS-CoV-2 immune response.…”
Section: Discussionmentioning
confidence: 99%